We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
-5
112
4
avatar+-18 

3.) Write an equation of the parabola with

 

a.) focus (0, –2) and directrix y = 2

 

b.) focus (3, 5) and directrix y = 7

 

c.) focus (–2, 1) and directrix y = 13

 Feb 20, 2019
 #1
avatar+101872 
+3

a.) focus (0, –2) and directrix y = 2

 

The directrix is above the focus so this parabola opens downward

 

The vertex is   halfway between the focus and the directrix....so it must be (0, 0)

 

"p" is the distance between the vertex and the focus [ or the vertex and the directrix ] =  2

 

So.....we have this form

 

4p ( y - k) = - ( x - h)^2         where (h, k) is the vertex and p = 2

 

So we have

 

4(2) ( y - 0) = - ( x - 0)^2          simplify

 

8y = -x^2         divide both sides by 8

 

y = -(1/8)x^2

 

 

cool cool cool

 Feb 20, 2019
 #2
avatar+101872 
+3

b.) focus (3, 5) and directrix y = 7

 

Again....the directrix is above the focus....so this turns downward

 

The vertex is hafway between the focus and directrix = (3, 6)

 

p =   distance between focus and vertex = 1

 

So we have

 

4p (y - k) =  -(x - h)^2             (h, k) = (3, 6)   and p = 1

 

4(1) (y - 6) = - (x - 3)^2

 

4 ( y - 6) = - ( x - 3)^2

 

y - 6 =  - ( 1/4)(x - 3)^2

 

y =   - (1/4) ( x - 3)^2 + 6

 

 

cool  cool   cool

 Feb 20, 2019
 #3
avatar-18 
-4

How about (c)? How do you do that one?

GAMEMASTERX40  Feb 20, 2019
 #4
avatar+101872 
+3

c.) focus (–2, 1) and directrix y = 13

 

turns downward

 

vertex =   ( - 2 ,  (13 + 1) / 2 )   =  ( -2, 14/2)   = ( -2, 7)

 

p =   6

 

4p ( y - 7) = - (x - - 2 )^2

 

4(6) ( y - 7) = - ( x + 2)^2

 

24 ( y - 7) = - ( x + 2)^2

 

y - 7=  - (1/24) ( x + 2)^2

 

y = - (1/24)( x + 2)^2 + 7

 

 

cool cool cool

 Feb 20, 2019

14 Online Users